Red cell distribution width to platelet count ratio as a predictor of severity in acute biliary pancreatitis: A cross sectional study in a tertiary care center - Acharya, Kalpana; Prajapati, Amit; Karna, Ekata; Maharjan, Shanta Bir (Journal of Surgery and Medicine, 2026)
Background/Aim: Acute biliary pancreatitis (AP) is an inflammatory condition of the pancreas with varying degrees of severity. Early detection of severe disease and timely intervention are crucial for improving outcomes. The red cell distribution width to platelet count ratio (RPR) is a proposed inflammatory marker that may be elevated in severe cases. This study aimed to evaluate the utility of RPR in predicting the severity of AP. Methods: This cross-sectional analytical study was conducted among 35 patients diagnosed with AP over one year. Patients were categorized into mild acute pancreatitis (MAP) and severe acute pancreatitis (SAP) groups. RPR was calculated upon admission, and outcomes were evaluated at the time of discharge or death. Results: Of the 35 patients, 14 (40%) had SAP. The mean RPR values for MAP and SAP were 0.05924 and 0.06525, respectively. There were four (11%) in-hospital deaths, all in the SAP group. The mean RPR for patients who died was 0.1291 (0.05208). The AUROC values of RPR for severity, ICU stay, and mortality were 0.609, 0.664, and 0.887, respectively. Conclusion: RPR can predict in-hospital mortality and ICU stay in patients with AP, but it is not sensitive in predicting the severity of the disease.